Integration of polymer nanocomposites technologies for automotive applications: opportunities and environmental health challenges - Njuguna, James A. K.; Peña, I.; Zhu, H.; Rocks, Sophie A.; Blazquez, Maria; Desai, S. A. (Cranfield University, 2008)
The concept of nanostructured materials design is gaining widespread importance among the automotive industry. Although employment of nanotechnology in current and future automotives will go long way in solving energy crises, it is necessary to understand both the hazards associated with nanomaterials and the levels of exposure that are likely to occur. The existing knowledge in these areas is quite limited and it will be necessary in the near future. This paper highlights these key issues and goes a long way in pointing recent activities on environmental risks of nanomaterials. Some research directions are given and existing automotive opportunities and applications explored.